2022
DOI: 10.3390/ijerph192215050
|View full text |Cite
|
Sign up to set email alerts
|

Lupus, DNA Methylation, and Air Pollution: A Malicious Triad

Abstract: The pathogenesis of systemic lupus erythematosus (SLE) remains elusive to this day; however, genetic, epigenetic, and environmental factors have been implicated to be involved in disease pathogenesis. Recently, it was demonstrated that in systemic lupus erythematosus (SLE) patients, interferon-regulated genes are hypomethylated in naïve CD4+ T cells, CD19+ B lymphocytes, and CD14+ monocytes. This suggests that interferon-regulated genes may have been epigenetically poised in SLE patients for rapid expression u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 172 publications
(219 reference statements)
0
2
0
Order By: Relevance
“…3 Numerous preclinical studies have found that exposure to heavy metals, fine PM and gaseous pollutants can harm lymphocytes. [29][30][31][32] Inhalation of pollutants stimulates the the bronchusassociated lymphoid tissue to produce pro-inflammatory cytokines and, more importantly, autoantibodies. 33 The first and probably most notable example of such association comes from the observed relationship between silica dust exposure and RA.…”
Section: Chronic Exposure and Risk Of Rheumatic Musculoskeletal Diseasesmentioning
confidence: 99%
“…3 Numerous preclinical studies have found that exposure to heavy metals, fine PM and gaseous pollutants can harm lymphocytes. [29][30][31][32] Inhalation of pollutants stimulates the the bronchusassociated lymphoid tissue to produce pro-inflammatory cytokines and, more importantly, autoantibodies. 33 The first and probably most notable example of such association comes from the observed relationship between silica dust exposure and RA.…”
Section: Chronic Exposure and Risk Of Rheumatic Musculoskeletal Diseasesmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is an autoimmune disease in which autoantibodies against self-structures are synthesized 1 . The etiopathogenesis of this disease is multifactorial, and infections are supposed to play an important role in this context, as microorganisms may stimulate the immune system.…”
Section: Introductionmentioning
confidence: 99%